Effects of 100 years of drainage on peat properties in a drained peatland forests in northern Sweden - Casselgård, Mikaela (2020)
Natural peatlands provide a small but persistent long-term carbon (C) sink. However, within the last century their extent in Sweden has declined by about 1.5-2.0 million hectares due to drainage activities. When a peatland is drained, the groundwater level is lowered which leads to changes in peat properties, increased microbial activity and larger C and nitrogen (N) losses. The resulting changes in the ecosystem also influence fauna and flora communities and reduce biodiversity. The overall aim of this master’s thesis was to investigate how 100 years of drainage has affected the physical and chemical properties of peat in a drained peatland forest (Trollberget) in northern Sweden. Analyses of peat bulk density, ash content, C content, N content, C:N ratio, δ13C and δ15N data were conducted in relation to ditch distance (i.e. 5, 25 and 50 m) and across the peat profile (up to a depth of -55 cm). Similar data were further available for comparison from a nearby natural mire (Degerö mire). The results showed significant differences in bulk density, C content and δ13C between the different distances from ditch. Specifically, most of these parameters (except for δ13C) indicated a generally stronger drainage effect and decomposition in samples further away from the ditch which is in contrast to expectation. This was also confirmed by the ash and N content as well as C:N ratio and δ15N data though the patterns were not as clear and statistically not significant. The δ13C data, on the contrary, suggested highest drainage effect and decomposition closer to the ditch. Across the vertical peat profile, significant differences were found for all of the studied variables at the drained peatland forest. It is interesting to note that the depth profiles of bulk density, ash and N content, C:N ratio and δ15N indicate that drainage and decomposition has been strongest in the upper ~10-30 cm layer. The comparison with the natural mire suggests that the drained site had significantly higher bulk density, due to lowering of the groundwater level and subsequent subsidence, compaction and decomposition of the peat. Similarly, higher C and N content and lower C:N ratio compared to the natural mire indicate that the peat is strongly decomposed at the drained site. In comparison to the natural mire, a significant difference could also be detected for the δ15N values with an enrichment of 15N occurring in the upper layer due to enhanced decomposition following drainage. Peat δ13C data on the other hand was rather similar between the drained and natural sites. Overall, this thesis results demonstrate manifold changes in peat physical and chemical properties following drainage of natural mires. While most of these could be associated with increased decomposition rates in the upper ~30 cm layer, additional impacts might occur in relation to hydrological variations on the site or in connection to the forest edge surrounding the site, which may further alter nutrient content and water supply at specific locations across the drained peatland site. In summary, it can be said that ditching of mires has significant effects on physical and chemical peat properties with important subsequent effects on peatland ecosystem functioning such as greenhouse gas emissions, hydrology and biodiversity.